A new approach of modeling supervisory control for manufacturing systems based on SysML - Xiaoshan Lu; Pietrac, Laurent; Niel, Eric (2017 22nd IEEE International Conference on Emerging Technologies and Factory Automation (ETFA), 2017)
The supervisory control theory is widely used to deal with problems of controller design in the field of discrete event systems. Despite the academic attention over last several decades, there were few application cases in real industrial systems. Some scientific results have shown the difficulties of implementation of Supervisory Control Theory (SCT) and proposed some possible solutions. On the other hand, the difficulty of using the theory for system engineers should also be taken into consideration. This paper presents a modeling approach of SCT based on SysML. Aimed at typical manufacturing systems, a three-level model template is proposed to bridge the gap between SCT and system design. For each template in the modeling library, there is one equivalent model in three levels: the SCT model level, the interface model level and SCT model level. The construction of modeling template is based on the prototype abstraction of typical manufacturing system elements. The transformation algorithms between each model level are given in the paper. The engineer can design the system by the standardized templates and modeling procedures in system engineering level. The correspondent SCT model will be created according to the transformation algorithm and computed the solution automatically. An example will be posed to validate the modeling methodology application at the end of the paper.